When breath becomes air - Paul Kalanithi (The Bodley Head, 2016)
"For readers of Atul Gawande, Andrew Solomon, and Anne Lamott, a profoundly moving, exquisitely observed memoir by a young neurosurgeon faced with a terminal cancer diagnosis who attempts to answer the question What makes a life worth living? At the age of thirty-six, on the verge of completing a decade's worth of training as a neurosurgeon, Paul Kalanithi was diagnosed with stage IV lung cancer. One day he was a doctor treating the dying, and the next he was a patient struggling to live. And just like that, the future he and his wife had imagined evaporated. When Breath Becomes Air chronicles Kalanithi's transformation from a naïve medical student "possessed," as he wrote, "by the question of what, given that all organisms die, makes a virtuous and meaningful life" into a neurosurgeon at Stanford working in the brain, the most critical place for human identity, and finally into a patient and new father confronting his own mortality. What makes life worth living in the face of death? What do you do when the future, no longer a ladder toward your goals in life, flattens out into a perpetual present? What does it mean to have a child, to nurture a new life as another fades away? These are some of the questions Kalanithi wrestles with in this profoundly moving, exquisitely observed memoir. Paul Kalanithi died in March 2015, while working on this book, yet his words live on as a guide and a gift to us all. "I began to realize that coming face to face with my own mortality, in a sense, had changed nothing and everything," he wrote. "Seven words from Samuel Beckett began to repeat in my head: 'I can't go on. I'll go on.'" When Breath Becomes Air is an unforgettable, life-affirming reflection on the challenge of facing death and on the relationship between doctor and patient, from a brilliant writer who became both. Advance praise for When Breath Becomes Air "Rattling, heartbreaking, and ultimately beautiful, the too-young Dr. Kalanithi's memoir is proof that the dying are the ones who have the most to teach us about life."--Atul Gawande "Thanks to When Breath Becomes Air, those of us who never met Paul Kalanithi will both mourn his death and benefit from his life. This is one of a handful of books I consider to be a universal donor--I would recommend it to anyone, everyone."--Ann Patchett"--